2011
DOI: 10.1038/ni.1990
|View full text |Cite
|
Sign up to set email alerts
|

IRF5 promotes inflammatory macrophage polarization and TH1-TH17 responses

Abstract: Polymorphisms in the gene encoding the transcription factor IRF5 that lead to higher mRNA expression are associated with many autoimmune diseases. Here we show that IRF5 expression in macrophages was reversibly induced by inflammatory stimuli and contributed to the plasticity of macrophage polarization. High expression of IRF5 was characteristic of M1 macrophages, in which it directly activated transcription of the genes encoding interleukin 12 subunit p40 (IL-12p40), IL-12p35 and IL-23p19 and repressed the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
994
9
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,112 publications
(1,057 citation statements)
references
References 49 publications
45
994
9
9
Order By: Relevance
“…However, the reason for the delayed signaling activation induced by IL-32g is still unclear, because no IL-32-specific receptor has yet been identified, although IL-32 was reported to interact with integrins such as aVb3 and aVb6 through its Arg-Gly-Asp (RGD) motif (42). Further functional and transcriptional analyses, including the expression of transcription factors, such as IRF4 (43) and IRF5 (44), are needed to understand how M-CSF and IL-32g influence each other during the regulation of the phenotypes and functions of macrophages. Despite these unresolved issues, the findings regarding the unique functional interplay between M-CSF and IL-32g presented in this article increase our understanding of the mechanisms that regulate the survival and M1/ M2 ratio of macrophages, as well as HIV-1 replication in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…However, the reason for the delayed signaling activation induced by IL-32g is still unclear, because no IL-32-specific receptor has yet been identified, although IL-32 was reported to interact with integrins such as aVb3 and aVb6 through its Arg-Gly-Asp (RGD) motif (42). Further functional and transcriptional analyses, including the expression of transcription factors, such as IRF4 (43) and IRF5 (44), are needed to understand how M-CSF and IL-32g influence each other during the regulation of the phenotypes and functions of macrophages. Despite these unresolved issues, the findings regarding the unique functional interplay between M-CSF and IL-32g presented in this article increase our understanding of the mechanisms that regulate the survival and M1/ M2 ratio of macrophages, as well as HIV-1 replication in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…In acid aspiration lung injury, TLR4/TRIF/TRAF6 signaling in lung macrophages was shown to determine the susceptibility to ARDS in vivo (12,33). Both TRAF6 and IRF5 lead to NF-kB activation, but IRF5 is also an important regulator of iNOS and IL-12b expression and, thus, M1 polarization (23,52,(57)(58)(59)(60). We found that WT macrophages upregulate TRAF6 and IRF5 gene expression in line with their M1 phenotype, whereas Akt2-deficient macrophages, having an M2 phenotype, exhibit reduced levels of these factors both at baseline and upon acid injury.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue macrophages display enormous functional and phenotypical plasticity in response to changing microenvironmental stimuli [42,43]. Under steady-state conditions, macrophages support either homeostatic processes or trophic processes for tissue development/remodeling in developing or healing tissues [4,5].…”
Section: Development and Functions Of Macrophagesmentioning
confidence: 99%